The Sopranos. Bonus features - Chase, David, 1945 August 22-; Winter, Terence; Coulter, Allen; Chianese, Dominic, 1931-; Iler, Robert, 1985-; Weiner, Matthew; Taylor, Alan, 1965-; Landress, Ilene S.; Falco, Edie.; Van Zandt, Steve; Turturro, Aida.; Baldwin, Alec, 1958-; et al. (New York : HBO Home Entertainment, 2009)
Tony faces a myriad of immediate, stress-inducing crises at home, at work and from the law. Tony's wife Carmela plans for a future she's not sure will arrive, and son AJ and daughter Meadow find that adulthood holds its own surprises.
Disc 2. Cut to the Chase: Alec Baldwin interviews David Chase -- Anatomy of the mob: Alec Baldwin interviews David Chase -- The Paley Center for Media seminar: Whacked Sopranos / David Chase and Terence Winter interviewed by Bryant Gumbel -- Extra gravy: Sopranos spoofs from episodes of The Simpsons, MadTV, and Saturday night live.
Originally broadcast on the HBO cable network in 2007.
Title from disc surface.
Not rated.
DVD ; region 1 ; widescreen presentation ; Dolby digital.
In English or dubbed into French or Spanish ; with optional subtitles in English, French or Spanish ; closed-captioned.
NEWV-TAYL
Keywords: Chase, David, -- 1945 August 22- -- Interviews; Sopranos (Television program); Television -- Production and direction; Television series; Video recordings for the hearing impaired; Gangster television programs; Interviews